2005
DOI: 10.1152/jn.00470.2005
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Mechanical Response of Muscle Thin-Fiber Sensory Receptors Recorded from Rat Muscle–Nerve Preparations In Vitro After Eccentric Contraction

Abstract: Taguchi, Toru, Jun Sato, and Kazue Mizumura. Augmented mechanical response of muscle thin-fiber sensory receptors recorded from rat muscle-nerve preparations in vitro after eccentric contraction. J Neurophysiol 94: 2822Neurophysiol 94: -2831Neurophysiol 94: , 2005 doi:10.1152/jn.00470.2005. Unaccustomed strenuous exercise, especially that from eccentric muscular work, often causes muscle tenderness, which is a kind of mechanical hyperalgesia. We developed an animal model of delayed-onset muscle soreness (DOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 54 publications
8
114
3
Order By: Relevance
“…However, since bradykinin, kallidin, and kallidin-like peptide bind B 2 bradykinin receptors, and B 2 antagonist cannot differentially block the action of these three, here we used "bradykinin" to refer to all three of these kinins. The absence of an effect from bradykinin receptor antagonists administered after development of DOMS showed that bradykinin is not the substance that maintains mechanical hyperalgesia, which means that bradykinin is not responsible for the increased mechanical sensitivity of thin-fiber receptors after LC (Taguchi et al, 2005b).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, since bradykinin, kallidin, and kallidin-like peptide bind B 2 bradykinin receptors, and B 2 antagonist cannot differentially block the action of these three, here we used "bradykinin" to refer to all three of these kinins. The absence of an effect from bradykinin receptor antagonists administered after development of DOMS showed that bradykinin is not the substance that maintains mechanical hyperalgesia, which means that bradykinin is not responsible for the increased mechanical sensitivity of thin-fiber receptors after LC (Taguchi et al, 2005b).…”
Section: Discussionmentioning
confidence: 98%
“…In the present experiment, we examined involvement of bradykinin and NGF in DOMS using a rat model of DOMS in which we previously showed the existence of mechanical hyperalgesia (Taguchi et al, 2005a) and increased mechanical sensitivity of muscle thin-fiber afferents (Taguchi et al, 2005b). We found that bradykinin triggers development of muscular mechanical hyperalgesia and NGF serves in its maintenance by sensitizing muscle C-fiber receptors to mechanical stimulation.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…2, 4-2). Previous animal experiments have revealed that the threshold of response of thin muscle afferents to mechanical stimuli was reduced in muscle with DOMS after ECC 49) . The exact mechanism responsible for the sensitization of thin muscle afferents to mechanical stimuli in muscles with DOMS has not yet been clarified.…”
Section: Muscle Pain (Doms Sensation) and Neurogenic Drivementioning
confidence: 90%